Response and progression on midostaurin in advanced systemic mastocytosis: KIT D816V and other molecular markers - Jawhar, Mohamad; Schwaab, Juliana; Naumann, Nicole; Metzgeroth, Georgia; Fabarius, Alice; Hofmann, Wolf-Karsten; Reiter, Andreas (Blood, 2017)
In advanced systemic mastocytosis (advSM), disease evolution is often triggered by KIT mutations (D816V in >80% of cases) and by additional mutations (eg, in SRSF2, ASXL1, and/or RUNX1 [S/A/Rpos in >60% of cases]). In a recently reported phase 2 study, midostaurin, a multikinase/KIT inhibitor, demonstrated an overall response rate (ORR) of 60% in advSM but biomarkers predictive of response are lacking. We evaluated the impact of molecular markers at baseline and during follow-up in 38 midostaurin-treated advSM patients. The median overall survival (OS) was 30 months (95% confidence interval, 6-54) from start of midostaurin. ORR and OS were significantly different between S/A/Rneg (n = 12) and S/A/Rpos (n = 23) patients (ORR: 75% vs 39%, P = .04; OS: P = .01, HR 4.5 [1.3-16.2]). Depending on the relative reduction of the KIT D816V expressed allele burden (EAB) at month 6, patients were classified as KIT responders (≥25%, n = 17) or KIT nonresponders (<25%, n = 11). In univariate analyses at month 6, reduction of KIT D816V EAB ≥25%, tryptase ≥50%, and alkaline phosphatase ≥50% were significantly associated with improved OS. In multivariate analysis, only KIT D816V EAB reduction ≥25% remained an independent on-treatment marker for improved OS (P = .004, HR 6.8 [1.8-25.3]). Serial next-generation sequencing analysis of 28 genes in 16 patients revealed acquisition of additional mutations or increasing variant allele frequency in K/NRAS, RUNX1, IDH2, or NPM1 associated with progression in 7 patients. In midostaurin-treated advSM patients, the complexity and dynamics of mutational profiles significantly affect response, progression, and prognosis.